Simulasi Numerik tentang pengaruh geometri mandibula yang direkonstruksi terhadap tegangan von Mises - Rakhmad Arief Siregar; Muhammad Yusuf Rahmansyah Siahaan; Riki Juliansyah (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
The study of mandibular reconstruction is known to be the most challenging procedure because a deformed chin may result in a person having low self-esteem. Despite advances in medical technology, there are always new trends related to mandibular implants. This study investigates the effect of reconstructed mandibular geometry on von Mises stress. There are three reconstructed mandibular models based on dental arches, square, ovoid and tapered to observe the distribution of von Mises stress. The three models were subjected to three varying loads around the alveolar ridge to simulate biting activity. The results show that geometric factors affect the distribution of von Mises stress, where the mandible with a tapered dental arch shows lower von Mises stress response compared to other mandibular models and has a significant effect when the applied load increases